Jewish Divorce Formulae in Syriac Incantation Bowls - Moriggi, Marco 1976- (2015)
In a series of Syriac incantation bowls published between 1913 and the present day, a peculiar text is documented. It mentions Rab Joshua bar Peraḥya sitting in a court of law and performing an exorcism against demons, devils, liliths and other evil beings haunting the house of the client. This spell is well attested in Jewish Babylonian Aramaic bowls, and it is now clear that a Jewish Babylonian Aramaic model is the basis for what is found in the Syriac bowls. The new edition of the Syriac bowls featuring this formula recently published by the present author, allows for a reconsideration of the theme of the Jewish divorce formula in Syriac incantation bowls, from both the linguistic and cultural points of view.
Keywords: Aramaic incantation bowls -- Syriac -- divorce formula -- late-antique Mesopotamia, magic and exorcism in the ancient world -- Jewish Babylonian Aramaic -- Sasanian Babylonia; Aramäische Beschwörungsschalen; Scheidungsformel